Shedding new light on the origin and spread of the brinjal eggplant (Solanum melongena L.) and its wild relatives - (:unkn) unknown (My University, 2018)
Premise of the study - While brinjal eggplant (Solanum melongena L.) is the second most important solanaceous fruit crop, we lack firm knowledge of its evolutionary relationships. This in turn limits efficient use of crop wild relatives in eggplant improvement. Here, we examine the hypothesis of linear step-wise expansion of the eggplant group from Africa to Asia.Methods - We use museum collections to generate nuclear and full-plastome data for all species of the Eggplant clade. We combine a phylogenomic approach with distribution data to infer a biogeographic scenario for the clade.Key results - The Eggplant clade has Pleistocene origins in northern Africa. Dispersals to tropical Asia gave rise to Solanum insanum, the wild progenitor of the eggplant, and to African distinct lineages of widespread and southern African species. Results suggest that spread of the species to southern Africa has been recent and likely facilitated by large mammalian herbivores, such as the African elephant and impala feeding on Solanum fruit.Conclusions - Rather than a linear 'Out Of Africa' sequence, our results are more consistent with an initial dispersal event into Asia, and subsequent wide dispersal and differentiation across Africa driven by large mammalian herbivores. Our evolutionary results will affect future work on eggplant domestication and affect the use of wild relatives in breeding of this increasingly important solanaceous crop.
Keywords: African Research